2014
DOI: 10.1186/2046-4053-3-92
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of small-volume red blood cell transfusions in the neonatal population

Abstract: BackgroundAdverse transfusion reactions in the neonatal population are poorly understood and defined. The incidence and pattern of adverse effects due to red blood cell (RBC) transfusion are not well known, and there has been no systematic review of published adverse events. RBC transfusions continue to be linked to the development of morbidities unique to neonates, including chronic lung disease, retinopathy of prematurity, intraventricular haemorrhage and necrotising enterocolitis. Uncertainties about the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…This review is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement . A full version of the review protocol has been published; therefore, only a summary of the review protocol is provided here.…”
Section: Methodsmentioning
confidence: 99%
“…This review is reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement . A full version of the review protocol has been published; therefore, only a summary of the review protocol is provided here.…”
Section: Methodsmentioning
confidence: 99%
“…One important aspect of the LBW infant's physiology is the occurrence of oxidative stress and hypocalcemia. Both can potentiate lead deposition and exacerbate its potential toxicity especially to the growing brain and skeletal system (9,14). Multivariate analysis revealed that blood creatinine level after transfusion was the best predictor of BLL% change.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Complications during NICU stay (9). (ii) Mortality: either mortality associated with receipt of PRBCs transfusion (within 24 -48 hours of receipt of a transfusion), which may be related to initial pathology or mortality before discharge from initial diagnosis or complications.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Over recent years, the association between the receipt of an RBC transfusion and development of NEC within the following 48 h has been well described and has been coined TANEC . However, systematic reviews examining whether primary studies support this association have arrived at conflicting conclusions . Despite this, potential interventions to decrease the risk of this potential entity have been explored, including withholding enteral feeds during transfusion.…”
Section: Commentarymentioning
confidence: 99%
“…5 However, systematic reviews examining whether primary studies support this association have arrived at conflicting conclusions. [5][6][7] Despite this, potential interventions to decrease the risk of this potential entity have been explored, including withholding enteral feeds during transfusion. As a consequence, there are reported clinical variations in clinical practices around continuing, reducing or withholding enteral feeds during neonatal transfusion.…”
Section: Commentarymentioning
confidence: 99%